PENGARUH METODE LATIHAN UP HILL & RUBBER TERHADAP PENINGKATAN KECEPATAN LARI SPRINT - Diki Yosep Pratama; Dicky Reva Apriana Sanga Dwi; Dedi Iskandar (STKIP Muhammadiyah Kuningan, 2020)
This study aims to determine the effect of the Uphill and Rubber training method in increasing students’ sprint running speed.This research is using experimental method. The study population was 64 students of MTs Riyadul Badiah grade IX. The sample was determined as many as 64 people. The sampling technique used simple random sampling, by taking samples from members of the population that was done randomly without paying attention to the strata in the population. The instrument used was a sprint assessment format. Data analysis using t test. The result showed that the application of the up hill training method had a better effect than the rubber training method in increasing the sprint running speed of students in class IX MTS Riyadul Badiah Karangkancana.